2016
DOI: 10.1016/j.poly.2016.01.023
|View full text |Cite
|
Sign up to set email alerts
|

A mixed valence zinc dithiolene system with spectator metal and reactor ligands

Abstract: Neutral complexes of zinc with N,N′-diisopropylpiperazine-2,3-dithione (iPr2Dt0) and N,N′-dimethylpiperazine-2,3-dithione (Me2Dt0) with chloride or maleonitriledithiolate (mnt2−) as coligands have been synthesized and characterized. The molecular structures of these zinc complexes have been determined using single crystal X-ray diffractometry. Complexes recrystallize in monoclinic P type systems with zinc adopting a distorted tetrahedral geometry. Two zinc complexes with mixed-valent dithiolene ligands exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…Comprehensive study of metal dithiolenes found that cobalt, nickel and iron complexes display most often square planar geometries, 47,48 whereas zinc complexes display tetrahedral geometries. [49][50][51] Cobalt dithiolene species are among the most efficient molecular catalysts for the hydrogen evolution reaction (HER). 44,45,52-54 A higher activity for HER was observed for the cobalt dithiolene complex, [Co(bdt) 2 ] − , in a 1 : 1 mixture of water and acetonitrile, relative to the activity in a pure anhydrous organic solvent (100% acetonitrile).…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive study of metal dithiolenes found that cobalt, nickel and iron complexes display most often square planar geometries, 47,48 whereas zinc complexes display tetrahedral geometries. [49][50][51] Cobalt dithiolene species are among the most efficient molecular catalysts for the hydrogen evolution reaction (HER). 44,45,52-54 A higher activity for HER was observed for the cobalt dithiolene complex, [Co(bdt) 2 ] − , in a 1 : 1 mixture of water and acetonitrile, relative to the activity in a pure anhydrous organic solvent (100% acetonitrile).…”
Section: Discussionmentioning
confidence: 99%
“…The C−C bond lengths of the Dt 0 moieties are similar in length to the C−C (C2‐C3) single bond of the methylene backbone of the Dt 0 ligand, which may be utilized as an “internal standard” for a C−C single bond. The C−S (C1‐S1 and C4‐S2) are of similar lengths to the C−S double bond observed in structurally characterized Dt 0 metal complexes, [3a,b,f–h,4a,b,5c,d] suggesting C−S double bond character. The bond distances and the 1 H NMR and IR spectral signatures suggest that the Dt 0 ligand maintains a fully oxidized in both solution and solid states.…”
Section: Discussionmentioning
confidence: 67%
“…S2 and S3 †). 31 The cyclic voltammogram of free i Pr 2 Dt 0 ligand exhibited two partially reversible reduction couples at À1887 mV (DE p ¼ 134 mV) and À2088 mV (DE p ¼ 141 mV), and [Zn(mnt)( i Pr 2 Dt 0 )] produces two partially reversible reduction couples at À939 mV (DE p ¼ 115 mV) and À1365 mV (DE p ¼ 125 mV). For 6 and [Zn(mnt)( i Pr 2 Dt 0 )], the ligand-based redox couples are shied by 802 mV and 948 mV, respectively for the rst couple and 604 mV and 723 mV for the second couple, respectively, compared to free i Pr 2 Dt 0 .…”
Section: Redox Chemistrymentioning
confidence: 98%